Colour polymorphism is associated with lower extinction risk in birds. (29th May 2017) - Ducatez, Simon; Giraudeau, Mathieu; Thébaud, Christophe; Jacquin, Lisa
Abstract: Colour polymorphisms have played a major role in enhancing current understanding of how selection and demography can impact phenotypes. Because different morphs often display alternative strategies and exploit alternative ecological niches, colour polymorphism can be expected to promote adaptability to environmental changes. However, whether and how it could influence populations' and species' response to global changes remains debated. To address this question, we built an up‐to‐date and complete database on avian colour polymorphism based on the examination of available data from all 10, 394 extant bird species. We distinguished between true polymorphism (where different genetically determined morphs co‐occur in sympatry within the same population) and geographic variation (parapatric or allopatric colour variation), because these two patterns of variation are expected to have different consequences on populations' persistence. Using the IUCN red list, we then showed that polymorphic bird species are at lesser risk of extinction than nonpolymorphic ones, after controlling for a range of factors such as geographic range size, habitat breadth, life history, and phylogeny. This appears consistent with the idea that high genetic diversity and/or the existence of alternative strategies in polymorphic species promotes the ability to adaptively respond to changing environmental conditions. In contrast, polymorphic species were not less vulnerable than nonpolymorphic ones to specific drivers of extinction such as habitat alteration, direct exploitation, climate change, and invasive species. Thus, our results suggest that colour polymorphism acts as a buffer against environmental changes, although further studies are now needed to understand the underlying mechanisms. Developing accurate quantitative indices of sensitivity to specific threats is likely a key step towards a better understanding of species response to environmental changes. Abstract : Based on a new complete database on birds' colour polymorphism, we show that polymorphic species, such as these Parasitic jaeger and Northern fulmar, are at lesser risk of extinction than nonpolymorphic species. The higher genetic variation we detected in polymorphic species might explain this result. In contrast, we could not detect any difference in polymorphic species vulnerability to specific extinction drivers (habitat destruction, direct exploitation, climate change or invasive species).